Energy absorption of sandwich structure under impact loading [electronic resource] - Nee, Siong Chee, 1986- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2010